"Der Sonnenstrahl mag die dunkle Stube nicht zu erhellen."
internationale Politik (allgemein);internationale Beziehungen;Entwicklungszusammenarbeit;Hilfswerk soziale Fragen;Leben in der Gesellschaft (allgemein);soziales Problem;Armut